Packet size adjustment strategy for fairness in multi-rate and multi-node IEEE 802.11 - XU Wei-qiang1; HU Si-ping1; WANG Ya-ming1; ZHANG Yun-hua1 (Tongxin xuebao)
After deeply analyzing the reasons of the unfairness in the multi-rate mechanism,the new strategy,transmission rate-based packet size adjustment（TRPSA） was provided.This strategy guaranteed that each node with different transmit rate could access the wireless channel fairly.The theoretic proof and the extensive simulation validation show that the proposed strategy can achieve the efficient fairness and improve the network performance under the multi-rate multi-node situation.The proposed strategy slightly modifies IEEE 802.11.Thus,it is easy to be implemented and widely applied in the practical network.